فقہ اسلامی میں جنگ و صلح کے معاہدہ کا تصور - پروفیسر محمد منیر (FIKR-O NAZAR فکر ونظر, 2009)
This article studies the law of peace treaties in the realm of International Law (Siyar) of Islam. Its findings show that the Imam can enter into a peace treaty with other states if it is beneficial for the Muslims and its provisions are not against the injunctions of the Shari’ah. According to the preferred opinion of Muslim fuqha’ the duration of a peace treaty is left to the discretion of the Imam to decide, keeping in view the interests of Muslim community. A Muslim state can terminate a treaty (a) on the expiry of its period; (b) if the other party breaches one of its fundamental provisions; (c) if the other party directly or indirectly assists a third party to wage war against the Muslims; (d) if the other party was hatching a conspiracy against the Muslims. Some Muslim jurists consider aman (pledge) as a kind of treaty. The agreement of jizyah (poll-tax) between non-Muslim citizens of a Muslim state and the Imam practically stands abolished in the modern world, as such non-Muslims are protected under the Constitutions of Muslim states.